Islamic Criminal Law on Sexual Bullying Involving Children: A Case Study of the Tasikmalaya Police - Nafsiyah, Ghina; Ristianawati, Eka (Pendidikan Agama Islam STIT Palapa Nusantara, 2026)
This study is motivated by the lack of research on sexual bullying perpetrated by minors, despite its growing prevalence and complex implications for child protection, juvenile justice, and Islamic criminal law in Indonesia. It aims to examine how Islamic criminal law conceptualizes child-perpetrated sexual bullying, how the Indonesian juvenile justice system handles such cases, and how both frameworks intersect in the practical context of policing at the Tasikmalaya Police. Employing a qualitative case study design, the research involved 25 purposively selected participants, including police officers, parents, community leaders, and social workers—and was conducted from September to November 2025. Data were collected through semi-structured interviews, non-participant observations, and document analysis, and were analyzed using the Miles, Huberman, and Saldana interactive model supported by NVivo 12. The findings reveal that both positive law and Islamic criminal law prioritize child protection but differ in assigning accountability: statutory law relies on restorative justice within legal boundaries, whereas Islamic law emphasizes ta’dīb, moral correction, and shared parental responsibility. Environmental instability, digital exposure, weakened supervision, and declining moral–religious formation are identified as major contributing factors to child-perpetrated sexual bullying. Diversion emerges as an effective child-friendly mechanism but is selectively applied due to the severity of victims’ trauma and institutional constraints. The study concludes that integrated legal–religious approaches are crucial for addressing sexual bullying involving minors, while acknowledging limitations related to the localized scope and reliance on qualitative interpretation. Future research is recommended to explore comparative models across regions and to develop culturally grounded intervention frameworks.